Glymphatic and neurofluidic dysfunction in classical trigeminal neuralgia: a multimodal MRI study of brain-CSF functional and structural dynamics - Fenyang Chen; Zhiliang Zhang; Jianliang Miao; Yvting Zhang; Ding Wang; Juncheng Yan; Lei Pan; Haiqi Ye; Zhongxiang Ding; Xiuhong Ge (BMC Medical Imaging)
Abstract Objective To investigate whether dysfunction of the glymphatic system and altered neurofluidic dynamics contribute to the pathophysiology of classical trigeminal neuralgia (CTN), and to explore the potential interplay between brain-CSF coupling and structural brain changes. Methods A total of 131 patients with CTN and 106 age- and sex-matched healthy controls were recruited. All participants underwent multimodal MRI, including high-resolution structural imaging, resting-state functional MRI, and diffusion tensor imaging. Key indices included choroid plexus (CP) volume as a proxy for CSF production, global BOLD-CSF coupling as a measure of functional neurofluidic interaction, and the DTI-based ALPS index reflecting glymphatic clearance. Additional markers included peak width of skeletonized mean diffusivity (PSMD) and global gray/white matter and CSF volume. Partial correlation analyses were performed between imaging metrics and clinical assessments. Results CTN patients showed significantly increased CP volume (P = 0.022) and gBOLD-CSF coupling (P < 0.001), along with reduced bilateral ALPS indices (P = 0.002, P = 0.004). PSMD and CSF volume were elevated (P < 0.001, P < 0.001), while gray and white matter volumes were reduced (P = 0.028, P = 0.009). gBOLD-CSF coupling correlated positively with depression, anxiety, and pain-related disability scores (P < 0.001), and negatively with MMSE (P = 0.022). Conclusion This study provides multimodal MRI evidence of glymphatic dysfunction and neurofluidic alterations in CTN, supporting a conceptual framework in which disrupted brain-CSF interaction may influence peripheral sensory modulation through a putative brain-CSF-ganglion pathway. These results may inform mechanistic hypotheses and guide future research on the neurofluidic underpinnings of neuropathic pain, potentially providing new insights into the pathogenesis of CTN.